Prospects for the use of bitumen modified with rubber granulate in a Two-Stage technological process - S. A. Ivanov (Вестник Дагестанского государственного технического университета: Технические науки, 2020)
Aim. This study was aimed at developing methods for improving the quality of bituminous binders by means of their modification. Methods. A method for regulating the process of destructing rubber granulate on an industrial scale, under which rubber granulate undergoes physical and chemical interactions with plasticized bitumen at a temperature of 230°C, was applied. Results. The article reviews existing publications devoted to the modification of petroleum road viscous bitumen with various polymers, in particular with rubber granulate obtained by processing waste of the rubber industry. The process of obtaining bitumen modified with rubber granulate through a two-stage technological process is described. The dependence of the physical and chemical parameters of the binder on the technological modes is estimated. The results of evaluating the structure of a modified binder, as well as the rubber granulate before and after thermomechanical processing, are presented. A comparison of the physical and chemical properties of bitumen modified with various rubber-granulate forms in a two-stage technological process with analogue products is presented. Conclusion. The proposed two-stage technological process of modifying bitumen with rubber granulate increases the homogeneity of the system and facilitates the formation of a dispersed framework reinforcing the binder, which leads to the production of a binder with improved physical and chemical characteristics. Rubber granulates impart an increased temperature stability and elasticity to the modified bitumen by means of forming tiny bumps on the surface of the particles.